2011
DOI: 10.1530/eje-10-1005
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vertebral fractures despite normal bone mineral density in patients with long-term controlled acromegaly

Abstract: Objective: To establish the prevalence of osteoporosis, vertebral fractures (VFs), and non-VFs in acromegaly patients with long-term controlled disease and factors potentially influencing fracture risk. Design: Case-control study. Patients and measurements: Eighty-nine patients (46% male, mean age: 58 years) were included. We studied VFs and non-VFs, bone mineral density (BMD), and markers of bone turnover. In 48 patients, BMD assessment was also obtained 7 years prior to the current study. To compare VF preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
100
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 39 publications
(51 reference statements)
11
100
0
6
Order By: Relevance
“…It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionsupporting
confidence: 74%
“…Recently, several studies have shown a marked increase in vertebral fracture prevalence and incidence for both sexes in acromegaly (5,31,32,33,34), related to the duration of disease activity and gonadal status among others. These observations underscore the complexity of a chronic and devastating disease as acromegaly, for bone as a target organ with fracture as the ultimate end point (2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations